Lojistik Firma Personellerinin Organik Tarım Anlayışı; Iğdır İli Örneği - Çavuşluk, Bayram; Karademir, Başaran (Turkish journal of agriculture : food science and technology, 2023)
Organic agricultural product is the food whose naturalness is certified and should not lose its naturalness until the end user. In this research, it was aimed to reveal the approach of the logistics (transport) sector employees to the transportation of organic agricultural products. The research was conducted in the form of a face-to-face survey on 115 logistics employees in Iğdır. The collected data were evaluated numerically and proportionally, and analyzed by statistical methods also including the decision tree CART algorithm. Logistics firm employees in the rate of 96.5% claimed to know what organic food is, 100% to eat organic food, and 59.1% even claimed to know what organic food certification is, but only 4.3% of the participants answered the question of "What do you think is organic food" as "organic certified food" for organic food, and 27.8% said that they pay attention to the certificate when purchasing organic food. Even, 27.8% of the participants claimed that they understood whether the food was organic when they looked at the product. Therewithal, 78.3% of the logistics employees stated that they do transportation of organic food and transportation time (94.8%), the cooling system (100%), and the cleanliness (100%) are more important criteria for organic food transportation compared to normal food. Apart from these, they stated that the employees of the sector other than themselves did not have sufficient knowledge (69.6%) about organic food transportation, while they claimed that they had sufficient knowledge (61.7%) about the subject. Consequently, although the logistics company employees in Iğdır region claimed that they knew organic food in general, it was revealed that their level of knowledge was not sufficient. Despite these results, it was observed that the personnel knew what to pay attention to in organic food transportation. It was concluded that the use of TV-Radio and the Internet could be used as a tool to eliminate the lack of information on the subject.